Investigating climate information services through a gendered lens - McOmber C; Panikowski A; McKune, Sarah; Bartels, W.; Russo, Sandra (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2013)
This paper explores access to climate change-related information through a gendered lens. Climate change is rapidly affecting the lives of farmers throughout the world, producing a need for adaptive agricultural livelihoods strategies. A central mechanism in the development of adaptive strategies to climate change is the strengthening and effective utilization of information channels. The more relevant and useful the information is to the user, the better the user may be able to adapt to changes in climate. Despite this critical need for accessing climate-related information, many of the people who are most vulnerable to climate change and environmental shocks are often on the periphery of receiving practical information. In this paper, we show that women farmers are overwhelmingly left out of many forms of communication channels. Thus, the purpose of this study is to identify instances in which methods of communication are missing women and how to overcome these gaps. What we propose is a context-dependent hybridization of traditional methods of communication, which are familiar to communities, and modern technologies, which can be expedient in sharing new scientific climate knowledge with farmers.